G442 'Think aki', an audit set up with epidemiological reasoning: Incidence of acute kidney injury in non-critically ill hospitalised children. (24th May 2017) - Pagkalis, S; Pottel, H; Hall, A; Bandi, S; Houtman, P; Vasista, P; Singh, N; Kannappan, H; Dolan, G; Bell, A; Faire, A; Ammari, C; et al.
Abstract : Aims: We aimed to estimate the incidence of Acute Kidney Injury (AKI) in an unselected paediatric population requiring admission to a large NHS hospital. Adult studies in the UK have shown significant under-detection of AKI cases. We wanted to see if this was the case for our population. Methods: The medical notes of 1779 children admitted consecutively to our hospital from November 2015 to February 2016, were retrospectively evaluated. Patients under seven days or older than 16 years of age, those with chronic kidney disease and all admissions to the neonatal unit were excluded. We assessed whether serum Creatinine (SCr) was measured when this was indicated according to the NICE Clinical-Guideline 169 for the prevention, detection and management of AKI. The study population size was based on literature research, according to which the incidence of AKI among non-critically ill hospitalised children may be at least 5%. AKI was recorded when SCr 1.5 times baseline. The baseline SCr was either a normal value obtained within six months prior to admission or the median SCr for each patient's age group. 41 children were admitted to our Paediatric Intensive Care Unit and 434 children were discharged directly from our Admissions Unit. Their data were audited but not used for the estimation of the incidence. Results: 876 patients were at risk of developing AKI and should have their SCr measured as per the NICE CG169. Our adherence was equal to 96.9%. A normal SCr value obtained within six months from admission was available for 224 children and a SCr difference 1.5 times was seen in 40 cases; of these, only one patient was clinically diagnosed with AKI. The incidence of AKI was found to be equal to 34/1304=2.6% [95% CI: 1.8, 3.6]. The median SCr for each patient's age group was used for this estimation. Conclusion: Our audit indicates that at least one in every fifty non-critical inpatients in paediatric wards has a degree of AKI. We found significant clinical under-detection of this problem.